Pengaruh Kegiatan Cooking Class Terhadap Perkembangan Motorik Halus Anak Di Taman Kanak-Kanak Negeri Pembina 01 Sutera - Sari, Minda; Marlina, Serli (Sekolah Tinggi Agama Islam Al-Kifayah Riau, 2023)
One of the most important aspects of child development to be stimulated is the aspect of physical motor development, namely fine motor. Children's fine motor development becomes optimal when they get the right stimulation. However, the activities at school are not maximal in stimulating children's fine motor skills, so other activities are needed that support the development of children's fine motor skills. Cooking class is an activity that can stimulate fine motor skills in children, because in this activity children will use their fingers when cleaning ingredients and eye and hand coordination when cutting ingredients. This type of Quasi Experimental research is a research method for researchers with quantitative research types. Groups B1 and B2 in this study were taken as samples. The experimental class is in Group B1 with 10 children and the control class is in Group B2 with 10 children. Data collection techniques in this study were in the form of tests and observations. Hypothesis testing uses the statistical technique T-test with the help of SPSS 20 which shows a significance level <0.05